Trade and Investment Implications of Brexit - World Bank Group (World Bank, Washington, DC, 2016)
The exit of the United Kingdom from the European Union (Brexit) may have a negative impact on trade and investment flows not just for the UK, but also for the countries with the largest exposure to the UK. The indirect impact of a Brexit-induced recession in the UK –may also be felt in the EU because of the two countries’ strong trade, investment, and financial linkages. The magnitude of these impacts will depend on the type of trade relationship that the UK negotiates with the EU, the duration of the negotiations, and the market confidence in the leadership of the UK, EU and other mayor players during the transition period. The major effect of the Brexit vote is the withdrawal of the UK from the EU project of deep economic integration, raising the possibility that the same doubts that gave rise to Brexit lead to an interruption of trade openness and integration in other parts of the world. International development institutions like the World Bank Group can play an important role in informing debates in this area.